Effect of Tuak Dayak on Testicular Organ Performance: In Vivo Study - Sius, Usu; Elisebath Wahyu Savitri; Rizkie Woro Hastuti (Open Access Indonesian Journal of Medical Reviews, 2022)
Tuak Dayak is an alcoholic drink that is often consumed by the people of West Kalimantan. Infertility is related to ROS levels as a result of alcohol oxidative stress. This study aims to determine the effect of tuak dayak on the 8-OHdG levels of semen and testicular weight. This research is an experimental study using experimental methods with a post-test-only randomized control group design. The research subjects were 25 rats, randomly divided into 5 groups. Group K0 was only given 3.6 mL/kgBW/day of distilled water, groups K1 and K2 were given Tuak Aren at doses of 1.8 and 3.6 mL/kgBW/day, and groups K3 and K4 were given Tuak Dayak at doses of 1.8 and 3.6 mL/kgBW/day. Treatment for 4 weeks. On day 29, semen and testes were taken. The testes are weighed with an electric weigher. Analysis of semen in the testes was performed to check the levels of 8-OHdG. The results of the Mann-Whitney test on K4 and K3 had no effect on the 8-OHdG content of cement. The average result in K4 was the number of Leydig cells 3.68±0.18, the thickness of the tubular tissue was 2.13±0.14µg, and the testicular weight was 0.91±0.09 g, the lowest. The average 8-OHdG content of cement was 0.22±0.01 ng/mL, the lowest was K2, and the highest was at K0 1.14±0.05 g/mL. In conclusion, Tuak Dayak had the effect of lowering testicular weight but did not show any effect on the activity of 8-hydroxy-2'deoxyguanosine (8-OHdG) in the semen of rats.